THE SHIFT AND EQUIVALENCE OF ENGLISH SENTENCE WORD ORDER AS IT IS TRANSLATED INTO INDONESIA - Suyudi, Suyudi (Journal of Language and Literature, 2017)
The problems of this research area:  Are there equivalence and shifts between the English and Indonesian word order in the translation of English sentences into Indonesian? And the aims of this research are to describe equivalence and shift between the English and Indonesia word order in the translation of English sentences into Indonesian. This research uses qualitative method, which is descriptive because it relates with word and sentences. This research analyze the equivalence and shift occurred in the translation of English sentences into Indonesian. The data is taken from the English novel the switch by Sandra Brown and its translated version by Monica Dwi Chresnayani. Data are classified into two categories, they are: Equivalence and shifts occurred in the translation of English sentence word order as it is translated into Indonesian. The number of equivalence of the word order is 37% and the number of shifts is 63%. We can conclude that the shifts occurred more than the equivalence.Keywords: Translation, shift, equivalence, word order.